ADOLESCENT MARRIAGES AND RISK OF STUNTING IN CHILDREN UNDER FIVE YEARS IN INDONESIA - Simbolon, Demsa; Riastuti, Frensi; Kusdalinah (Universitas Airlangga, 2024)
Introduction. The 2018 Basic Health Research Report recorded that 58.8% of women aged 10-19 years had been pregnant and 25.2% were pregnant. Aims: The study aimed to determine the relationship between adolescent marriage and the risk of stunting in Indonesia. Method. This research used Indonesian Family Life Survey (IFLS) 2014 data with a cross-sectional approach. The study sample was 4,809 children who met the inclusion criteria, such as biological children, live births, children aged 1-5 years in the 2014 IFLS, children living with biological parents, complete data on the child's length or height, data on the characteristics of the child, mother, and family, the child does not have a disease. Independent variable is the age of the mother at marriage. The dependent variable is the incidence of stunting. Bivariate analysis used the Chi-Square test and multivariate analysis used logistic regression. Result. The risk of stunting in children under five years in Indonesia in 2014 was 36.6%. The risk of stunting is higher in children under five years of married mothers in adolescence (42.4%) compared to mothers who are married at an old age (35%). Adolescent marriage is associated with the risk of stunting in children under five years, married adolescents have a 1.2 times risk of stunting compared to mothers who are married at an older age (p-value 0.046). Conclusion. Adolescent marriage increases the risk of stunting. Cross-sectoral integrated interventions are needed to implement the marriage age maturity program to prevent adolescent marriages to reduce the risk of stunting